analisis ANALISIS FULL COSTING METHOD SEBAGAI PENETAPAN HARGA JUAL LELE DUMBO DESA SPANDI KECAMATAN REMBANG KABUPATEN PASURUAN: ANALISIS FULL COSTING METHOD SEBAGAI PENETAPAN HARGA JUAL LELE DUMBO DESA SPANDI KECAMATAN REMBANG KABUPATEN PASURUAN - Ishak, Ishak; Khamdan Suriyok; Elsa Nur Syafrilia (Institut Teknologi dan Bisnis Yadika, 2025)
Competition in the Dumbo catfish farming business requires entrepreneurs to have an accurate pricing strategy in order to survive and obtain optimal profits. However, in practice, many businesses still determine their selling price based solely on market prices without accurately calculating the cost of goods sold (COGS). This condition has the potential to cause errors in profit calculations and impact business decision-making. This study aims to analyze the calculation of COGS among catfish farmers in Spandi Village, Rembang District, using the Full Costing method as a basis for more accurate pricing. The study uses a qualitative descriptive approach by collecting primary data through interviews, observation, and documentation. The data collected covers all components of production costs, such as raw material costs, direct labor costs, and factory overhead costs. The analysis was carried out through data reduction, data presentation, and systematic conclusion drawing. The results show that Lele Dumbo entrepreneurs have not calculated COGS in accordance with the Full Costing principle. The production cost calculations did not include all cost elements, especially overhead costs, which should have been taken into account. In addition, the selling price was not based on production cost calculations but followed market prices, thus not reflecting the optimal expected profit. In conclusion, the application of the Full Costing method provides more complete production cost information and can be used as a more accurate basis for determining the selling price so that the business can achieve maximum profits.